HUBUNGAN KEKUATAN OTOT PERUT DAN KELENTUKAN PINGGANGDENGAN KEMAMPUAN HEADING PERMAINAN SEPAK BOLA PADA SISWA EKSTRAKURIKULER PUTRA SMA NEGERI 13 PALEMBANG - Dede Dwiansyah Putra (STKIP ROKANIA, 2017)
This study aims to determine the relationship of abdominal muscle strength and hip flexibility with the ability to play football heading in extracurricular student of SMAN 13 Palembang. The method used to produce a particular product, and test the efficacy of the product, this study using research correlation methods. Populasi in this study were 30 persons who follow extracurricular activities SMAN 13 Palembang. Results showed r(x_1 y) = 0.461, r(x_2 y)=0.414 In abdominal muscle strength contributes to the ability of the ball (heading) of 46.1%. While the contribution of flexibility waist with ball (Heading) amounted to 41.4%. Based on t greater than t table (2.46>1.77) for the contribution of abdominal muscle strength by heading ability. As for flexibility waist with heading ability was tested significance of t greater than ttable (2.40> 1.77).